Hadith #697 - Sahih Muslim - Ja'far bin 'Amr bin Umayya جعفر بن عمرو بن أمية (Sahih Muslim)
I saw the Messenger of Allah (ﷺ) take slices from goat’s shoulder, and then eat them, and then offer prayer without having performed ablution.
Grade: Sahih

Hadith #698 - Sahih Muslim - Ja'far bin 'Amr bin Umayya جعفر بن عمرو بن أمية (Sahih Muslim)
I saw the Messenger of Allah (ﷺ) take slices from goat’s shoulder and then eat them. He was called for prayer and he got’up, leaving aside the knife, and offered prayer but did not perform ablution.
Grade: Sahih